An Automatic Generation Of G1 Curve Fitting Of Arabic Characters Using Rational Bezier Cubic With Weight Adjustments. - Yahya, Fatimah; Md. Ali, Jamaludin; Ibrahim, Arsmah (2005)
An Arabic font is diflicult to fit as it is cursive in character, having varying curves and cusps. Here, the Arabic character is represented as an outline font fitted with rational Bezier cubic curves